The Effect of Using Mental Training According to Specific Areas on the Development of Soccer Players’ Tactical Performance - Abdul Hussein, Mohammed (Journal of Physical Education, 2016)
The importance of the research lies in using mental practice on developing tactical performance using proper models and coordinating between mental training and tactical performance in soccer. The aim of the research is to identify special exercises on the development on tactical performance of soccer players. The researchers hypothesized statistical differences in controlling and experimental groups in posttests. The researcher used the experimental method and conducted a pilot study followed by the training program and ended with the posttests. The data was collected and treated using proper statistical methods. The researchers concluded that mental training developed tactical performance in soccer players. Finally the researchers recommended including mental training programs in soccer training along with physical, tactical and technical aspects.